Structural elucidation approaches in carbohydrates: A comprehensive review on techniques and future trends - Liu, Yuning; Huang, Yajun; Zhu, Ruiyu; Farag, Mohamed A.; Capanoglu, Esra; Zhao, Chao (Food chemistry, 2023)
Carbohydrates and their implications for human health have been the subject to a rapidly growing interest. Substantial advances in analytical methods have enabled a more effective assessment of carbohydrates and their pharmacological effects. Developing a carbohydrate profile technology would surely aid the understanding of carbohydrate dietary impacts. With the advances in technology for characterization, as well as exploration of complex structure, it is becoming more feasible to synthesize such compounds, rather than isolation. Several technological developments, including improved analytical tools, glycomics, and automation technology, have opened up new opportunities to globally assess most carbohydrates in envisaged samples. The main analytical methods applied to carbohydrates are described. And then the development of automation technology in glycan synthesis are introduced. This review concludes by considering the limitations of the existing technologies and required future developments for overcoming these limitations and improving identification score and/or yield.Carbohydrates and their implications for human health have been the subject to a rapidly growing interest. Substantial advances in analytical methods have enabled a more effective assessment of carbohydrates and their pharmacological effects. Developing a carbohydrate profile technology would surely aid the understanding of carbohydrate dietary impacts. With the advances in technology for characterization, as well as exploration of complex structure, it is becoming more feasible to synthesize such compounds, rather than isolation. Several technological developments, including improved analytical tools, glycomics, and automation technology, have opened up new opportunities to globally assess most carbohydrates in envisaged samples. The main analytical methods applied to carbohydrates are described. And then the development of automation technology in glycan synthesis are introduced. This review concludes by considering the limitations of the existing technologies and required future developments for overcoming these limitations and improving identification score and/or yield.